Preparation method of high-quality mullite brick for glass kiln

The problem of poor slag resistance bricks in the lining of glass kilns is solved by melt casting and the high temperature of mullite bricks is achieved. Improved resistance and corrosion resistance.

CN119462114APending Publication Date: 2025-02-18JIANGSU NUOMING HIGH TEMPERATURE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665392.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing refractory bricks are severely worn and chemically eroded due to poor slag corrosion resistance in the glass kiln lining, and the molten glass liquid penetrates into the brick and reduces the insulation performance and shortens the service life.

Method used

Preparation of high-quality mullite bricks by melt casting. By adding silicon nitride/calcium carbonate composite particles during the melt cooling process, the release of carbon dioxide disturbs the melt, release internal gas and evenly diffuse the composite particles, thereby improving the high temperature resistance of the bricks. and corrosion resistance.

Benefits of technology

It effectively reduces residual gas inside mullite bricks, avoids defects, and improves the bricks' high temperature and corrosion resistance, and extends its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to a preparation method of a high-quality mullite brick for a glass kiln, which comprises the following steps: S1, proportioning: mixing 60-75 parts by weight of mullite powder, 6-10 parts by weight of magnesium oxide, 4-8 parts by weight of zircon sand, 2-5 parts by weight of laterite and 1-3 parts by weight of sodium bicarbonate to obtain a mixture; s2, melting: melting the mixture to obtain molten liquid; s3, pouring is conducted, specifically, the molten liquid is poured into a mold, and a cavity of the mold is fully filled with the molten liquid; and S4, crystallization: cooling the melt in the mold to room temperature to obtain the mullite brick. The mullite brick is prepared by casting, and the silicon nitride / calcium carbonate composite particles are added when the melt is cooled, so that gas in the melt can be fully released, and meanwhile, the release of carbon dioxide can enable the silicon nitride / calcium carbonate composite particles to be uniformly diffused into the melt, so that the high temperature resistance and erosion resistance of the mullite brick are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to a method for preparing high-quality mullite bricks used in a glass kiln. Background Art

[0002] Glass is mainly made of quartz sand and soda ash as raw materials through high-temperature melting. Glass kiln is the equipment for melting glass. There are many types of glass kilns, such as tank kilns, crucible kilns, etc. In the process of melting glass, refractory bricks are needed as the lining of the glass kiln.

[0003] However, because molten glass and glass raw materials are highly corrosive, and existing refractory bricks have poor resistance to slag erosion, the lining of the glass kiln will be subject to severe wear and chemical erosion. In this process, the molten glass liquid will also penetrate into the interior of the refractory bricks, resulting in reduced thermal insulation performance of the refractory bricks and shortened service life. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing high-quality mullite bricks for glass kiln.

[0005] The technical solution of the present invention is: a method for preparing high-quality mullite bricks for glass kilns, comprising the following steps:

[0006] S1. Ingredients

[0007] By weight, 60 to 75 parts of mullite powder, 6 to 10 parts of magnesium oxide, 4 to 8 parts of zircon sand, 2 to 5 parts of ferrous bauxite, and 1 to 3 parts of sodium bicarbonate are mixed to obtain a mixture;

[0008] S2, Melting

[0009] The mixed material is placed in an electric arc furnace, heated to 2000-2200°C, and the mixed material is melted to obtain a molten liquid;

[0010] S3. Pouring

[0011] Preheat the mold, and then pour the molten metal into the mold so that the molten metal fully fills the mold cavity;

[0012] S4, Crystallization

[0013] S4-1, keeping the mold at 1800-1900°C for 30-40 minutes, adding silicon nitride / calcium carbonate composite particles to the melt once after the heat preservation is completed, then stopping the heat preservation and vibrating the mold once for 2-4 minutes, and waiting for the melt temperature in the mold to drop to X after the vibration is completed; wherein, the single addition amount of silicon nitride / calcium carbonate composite particles accounts for 0.3-0.6% of the total mass of the melt in the mold, and the initial value of X is 1600-1700°C;

[0014] S4-2, repeat the cycle S4-1, and then each time the value of X is reduced by 50-80°C compared with the previous time, until X≤1400°C, so that the molten metal in the mold is quickly cooled to 800-850°C, and then the molten metal in the mold is naturally cooled to room temperature to obtain a mullite brick.

[0015] Description: The present invention prepares mullite bricks by melting and casting, and adds silicon nitride / calcium carbonate composite particles when the melt is cooled, and decomposes the calcium carbonate in the silicon nitride / calcium carbonate composite particles into calcium oxide and carbon dioxide at high temperature through multiple heating and cooling. The melt is disturbed by the release of carbon dioxide, so that the gas in the melt can be fully released, the residual gas in the mullite brick is reduced, and defects in the mullite brick are avoided. At the same time, the release of carbon dioxide can make the silicon nitride / calcium carbonate composite particles diffuse evenly into the melt, and silicon nitride and calcium oxide can react at high temperature to generate calcium nitride and disperse in the mullite brick, thereby improving the high temperature resistance and corrosion resistance of the mullite brick.

[0016] Furthermore, in step S2, the melting and casting voltage of the electric arc furnace is 150-200V, and the current is 1800-2000A.

[0017] Note: The above electric arc furnace parameters can ensure that the mixture is fully melted and avoid inclusions inside the mixture.

[0018] Furthermore, in step S3, the preheating temperature is 400-480° C., and the preheating time is 20-30 minutes.

[0019] Note: Preheating can reduce the gas in the mold, improve the casting quality, and avoid defects inside the mullite brick.

[0020] Furthermore, in step S1, the aluminum-silicon ratio of the mullite powder is 1.3-1.6:1, and the particle size of the mullite powder is 1-3 mm.

[0021] Note: Limiting the aluminum-silicon ratio of mullite powder can ensure the composition of mullite bricks and the strength of mullite bricks.

[0022] Furthermore, in step S4-1, the method for preparing the silicon nitride / calcium carbonate composite particles comprises the following steps:

[0023] 1) Add silicon tetrachloride into xylene and stir for 5 to 10 minutes, then put the mixture of silicon tetrachloride and xylene into a closed reactor, and introduce liquid ammonia into the mixture to react for 1 to 2 hours, take the mixture out of the closed reactor, extract the unreacted liquid ammonia on the upper layer, and obtain a precursor solution; wherein the mass ratio of silicon tetrachloride, xylene, and liquid ammonia is 1:3 to 4:1.2 to 1.6;

[0024] 2) adding calcium oxide and deionized water into the precursor solution, and then continuously passing carbon dioxide into the precursor solution. During the process of passing carbon dioxide, when the pH value of the precursor solution is less than 8, the pH value of the precursor solution is further adjusted to 9-10 using ammonia water with a mass concentration of 20-30%, and after aeration for 25-35 minutes, filtering to obtain solid particles; wherein the mass ratio of the precursor solution, calcium oxide, and deionized water is 1:0.3-0.4:0.6-0.8;

[0025] 3) calcining the solid particles at 250-300° C. for 30-40 min to obtain silicon nitride / calcium carbonate composite particles.

[0026] Description: The above method uses silicon tetrachloride as a silicon source and liquid ammonia as a nitrogen source, and after calcium oxide reacts with ammonia water, carbon dioxide is introduced to prepare silicon nitride / calcium carbonate composite particles. The calcium carbonate in the silicon nitride / calcium carbonate composite particles can be decomposed into calcium oxide and carbon dioxide at high temperature. The melt is disturbed by carbon dioxide to release the gas in the melt while uniformly dispersing the silicon nitride / calcium carbonate composite particles into the melt. Silicon nitride can react with calcium oxide at high temperature to generate calcium nitride, thereby improving the high temperature resistance and corrosion resistance of mullite bricks.

[0027] Furthermore, in step S4.1, the vibration frequency is 5 to 8 Hz, and the vibration amplitude is 2 to 4 mm.

[0028] Note: Vibration can increase the gas release rate in the melt, and limiting the vibration frequency can prevent the melt from shaking too violently and causing it to splash out.

[0029] Furthermore, in step S4.3, the rapid cooling method is to use compressed air at 10 to 15° C. to spray the mold surface, and the air flow velocity of the spray is 4 to 6 m / s.

[0030] Description: Using compressed air to spray the mold surface can make the molten liquid cool and crystallize quickly, so as to reduce the internal grain size of the mullite brick and improve the performance of the mullite brick.

[0031] The beneficial effects of the present invention are:

[0032] (1) The present invention prepares mullite bricks by melting and casting, and adds silicon nitride / calcium carbonate composite particles when the melt is cooled, so that the gas in the melt can be fully released, reducing the residual gas inside the mullite bricks. At the same time, the release of carbon dioxide can make the silicon nitride / calcium carbonate composite particles evenly diffuse into the melt, thereby improving the high temperature resistance and corrosion resistance of the mullite bricks.

[0033] (2) The calcium carbonate in the silicon nitride / calcium carbonate composite particles of the present invention can be decomposed into calcium oxide and carbon dioxide at high temperature. The melt is disturbed by carbon dioxide, and the gas in the melt is released while the silicon nitride / calcium carbonate composite particles are evenly dispersed into the melt. Silicon nitride can react with calcium oxide at high temperature to generate calcium nitride, thereby improving the high temperature resistance and corrosion resistance of mullite bricks. DETAILED DESCRIPTION

[0034] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0035] Embodiment 1: A method for preparing high-quality mullite bricks for glass kiln, comprising the following steps:

[0036] S1. Ingredients

[0037] 70 parts of mullite powder, 5 parts of magnesium oxide, 6 parts of zircon sand, 4 parts of bauxite and 2 parts of sodium bicarbonate are mixed by weight to obtain a mixture; wherein the aluminum-silicon ratio of the mullite powder is 1.5:1, and the particle size of the mullite powder is 1 to 3 mm;

[0038] S2, Melting

[0039] The mixed material is placed in an electric arc furnace, heated to 2100°C, and the mixed material is melted to obtain a molten liquid; wherein the melting and casting voltage of the electric arc furnace is 180V and the current is 1900A;

[0040] S3, pouring

[0041] The mold is preheated, and then the molten liquid is poured into the mold so that the molten liquid fully fills the mold cavity; wherein the preheating temperature is 440°C and the preheating time is 25 minutes;

[0042] S4, Crystallization

[0043] S4-1, the mold is kept at 1850°C for 35 minutes, and after the heat preservation is completed, silicon nitride / calcium carbonate composite particles are added to the melt once, and then the heat preservation is stopped and the mold is vibrated once for 3 minutes. After the vibration is completed, the temperature of the melt in the mold drops to X; wherein, the single addition amount of silicon nitride / calcium carbonate composite particles accounts for 0.45% of the total mass of the melt in the mold, the initial value of X is 1600-1700°C, the vibration frequency is 6 Hz, and the vibration amplitude is 3 mm;

[0044] S4-2, repeating S4-1, and then each time the value of X is reduced by 50-80°C compared with the previous time, until X≤1400°C, so that the molten metal in the mold is quickly cooled to 825°C, and then the molten metal in the mold is naturally cooled to room temperature to obtain a mullite brick; wherein the method of rapid cooling is to use 12°C compressed air to spray the mold surface, and the air flow velocity of the spray is 5m / s;

[0045] The preparation method of silicon nitride / calcium carbonate composite particles comprises the following steps:

[0046] 1) Add silicon tetrachloride into xylene and stir for 8 minutes, then put the mixture of silicon tetrachloride and xylene into a closed reactor, and introduce liquid ammonia into the mixture to react for 1.5 hours, take the mixture out of the closed reactor, extract the unreacted liquid ammonia on the upper layer, and obtain a precursor solution; wherein the mass ratio of silicon tetrachloride, xylene and liquid ammonia is 1:3.5:1.4;

[0047] 2) Calcium oxide and deionized water are added to the precursor solution, and then carbon dioxide is continuously introduced into the precursor solution. During the introduction of carbon dioxide, when the pH value of the precursor solution is less than 8, the pH value of the precursor solution is further adjusted to 9.5 using ammonia water with a mass concentration of 25%, and after ventilation for 30 minutes, solid particles are obtained by filtering; wherein the mass ratio of the precursor solution, calcium oxide, and deionized water is 1:0.35:0.7; wherein the flow rate of carbon dioxide is 1.5 L / min;

[0048] 3) calcining the solid particles at 280° C. for 35 min to obtain silicon nitride / calcium carbonate composite particles.

[0049] Example 2: This example is basically the same as Example 1, except that 60 parts of mullite powder, 6 parts of magnesium oxide, 4 parts of zircon sand, 2 parts of ferrous bauxite and 1 part of sodium bicarbonate are mixed to obtain a mixture.

[0050] Example 3: This example is basically the same as Example 1, except that 75 parts of mullite powder, 10 parts of magnesium oxide, 8 parts of zircon sand, 5 parts of ferrous bauxite, and 3 parts of sodium bicarbonate are mixed to obtain a mixture.

[0051] Example 4: This example is basically the same as Example 1, except that the aluminum-silicon ratio of the mullite powder is 1.3:1.

[0052] Example 5: This example is basically the same as Example 1, except that the aluminum-silicon ratio of the mullite powder is 1.6:1.

[0053] Example 6: This example is basically the same as Example 1, except that the single addition amount of silicon nitride / calcium carbonate composite particles accounts for 0.3% of the total mass of the molten metal in the mold.

[0054] Example 7: This example is basically the same as Example 1, except that the single addition amount of silicon nitride / calcium carbonate composite particles accounts for 0.6% of the total mass of the molten metal in the mold.

[0055] Example 8: This example is basically the same as Example 1, except that the initial value of X is 1600°C.

[0056] Example 9: This example is basically the same as Example 1, except that the initial value of X is 1700°C.

[0057] Example 10: This example is basically the same as Example 1, except that the value of X is reduced by 50° C. each time thereafter compared with the previous time.

[0058] Example 11: This example is basically the same as Example 1, except that the value of X is reduced by 80°C each time thereafter compared with the previous time.

[0059] Example 12: This example is basically the same as Example 1, except that compressed air at 12°C is used to spray the mold surface, and the air flow velocity of the spray is 4m / s.

[0060] Example 13: This example is basically the same as Example 1, except that compressed air at 12°C is used to spray the mold surface, and the air flow velocity of the spray is 6m / s.

[0061] Example 14: This example is basically the same as Example 1, except that when the pH value of the precursor solution is less than 8, the pH value of the precursor solution is further adjusted to 9 using ammonia water with a mass concentration of 25%.

[0062] Example 15: This example is basically the same as Example 1, except that when the pH value of the precursor solution is less than 8, the pH value of the precursor solution is further adjusted to 10 using ammonia water with a mass concentration of 25%.

[0063] Example 16: This example is basically the same as Example 1, except that the mass ratio of the precursor solution, calcium oxide, and deionized water is 1:0.3:0.6.

[0064] Example 17: This example is basically the same as Example 1, except that the mass ratio of the precursor solution, calcium oxide, and deionized water is 1:0.4:0.8.

[0065] Example 18: This example is basically the same as Example 1, except that the flow rate of carbon dioxide is 1 L / min.

[0066] Example 19: This example is basically the same as Example 1, except that the flow rate of carbon dioxide is 2 L / min.

[0067] Comparative Example 1: Using Example 1 as a reference, no silicon nitride / calcium carbonate composite particles are added to the melt after the insulation is completed.

[0068] Comparative Example 2: Taking Example 1 as a reference, the silicon nitride / calcium carbonate composite particles were replaced with silicon nitride particles and calcium carbonate particles.

[0069] Comparative Example 3: Taking Example 1 as a reference, after the vibration is completed, the temperature of the melt in the mold continues to drop to 1400°C.

[0070] Comparative Example 4: Using Example 1 as a reference, the pH value of the precursor solution was not adjusted during the introduction of carbon dioxide.

[0071] Experimental Example: In order to explore the influence of the parameters of each embodiment on the performance of mullite bricks, the erosion rate of the mullite bricks prepared in each embodiment was tested at 1200°C using the static crucible method, and the strength of the mullite bricks in each embodiment was tested. The specific exploration is as follows:

[0072] Experimental Example 1: Investigating the influence of composition on the performance of mullite bricks

[0073] Using Examples 1 to 5 as experimental comparison, the performance of mullite bricks under different compositions is shown in Table 1 below:

[0074] Table 1 Properties of mullite bricks under different compositions

[0075] Group Compressive strength / MPa Erosion rate Example 1 293 0.83 Example 2 265 1.12 Example 3 274 0.95 Example 4 249 1.25 Example 5 261 0.97

[0076] It can be seen from the data in Table 1 that, compared with Examples 1 to 5, the composition of the mullite brick and the aluminum-silicon ratio of the mullite powder will affect the performance of the mullite brick. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the mullite brick composition and the aluminum-silicon ratio of the mullite powder selected in Example 1 are both optimal.

[0077] Experimental Example 2: Investigating the effect of silicon nitride / calcium carbonate composite particle addition on the performance of mullite bricks

[0078] Using Example 1, Examples 6-7 and Comparative Examples 1-2 as experimental comparisons, the performance of the mullite bricks obtained with different addition amounts of silicon nitride / calcium carbonate composite particles is shown in Table 2 below:

[0079] Table 2 Properties of mullite bricks with different addition amounts of silicon nitride / calcium carbonate composite particles

[0080] Group Compressive strength / MPa Erosion rate Example 1 293 0.83 Example 6 279 0.95 Example 7 246 1.27 Comparative Example 1 208 1.68 Comparative Example 2 223 1.53

[0081] It can be seen from the data in Table 2 that, compared with Examples 1, 6, and 7: Too high or too low an addition amount of silicon nitride / calcium carbonate composite particles will lead to a decrease in the performance of the mullite brick. This may be because too low an addition amount of silicon nitride / calcium carbonate composite particles will lead to insufficient release of the gas in the melt, while too high an addition amount of silicon nitride / calcium carbonate composite particles will lead to excessive gas in the melt, resulting in more defects inside the mullite brick. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the addition amount of silicon nitride / calcium carbonate composite particles selected in Example 1 is the best;

[0082] Example 1 compared with Comparative Examples 1 and 2: After not adding silicon nitride / calcium carbonate composite particles or replacing the silicon nitride / calcium carbonate composite particles with silicon nitride particles and calcium carbonate particles, the performance of the mullite brick is significantly reduced. This may be because silicon nitride particles and calcium carbonate particles are added separately, and the silicon nitride particles cannot be evenly dispersed in the mullite brick, resulting in the silicon nitride particles being unable to fully react with calcium oxide.

[0083] Experimental Example 3: Investigating the influence of crystallization temperature on the performance of mullite bricks

[0084] Using Example 1, Examples 8 to 13 and Comparative Example 3 as experimental comparisons, the properties of mullite bricks at different crystallization temperatures are shown in Table 3 below:

[0085] Table 3 Properties of mullite bricks at different crystallization temperatures

[0086] Group Compressive strength / MPa Erosion rate Example 1 293 0.83 Example 8 281 0.92 Example 9 277 1.02 Example 10 265 1.07 Embodiment 11 271 0.98 Example 12 268 1.06 Embodiment 13 264 1.12 Comparative Example 3 220 1.59

[0087] It can be seen from the data in Table 3 that, compared with Example 1 and Examples 8 to 11, the initial value of the melt temperature is too high or too low, and the temperature change of the melt temperature is too high or too low, which will lead to the performance of the mullite brick to decrease. This may be because the silicon nitride / calcium carbonate composite particles in the melt cannot fully react. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the initial value of the melt temperature and the temperature change of the melt temperature selected in Example 1 are both optimal;

[0088] Compared with Examples 1, 12, and 13: Too high or too low airflow velocity will lead to a decrease in the performance of the mullite brick. This may be because too high an airflow velocity will cause the melt to cool too quickly, causing defects inside the mullite brick, while too low an airflow velocity will cause coarse grains inside the mullite brick. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the airflow velocity selected in Example 1 is the best;

[0089] Compared with Comparative Example 3, Example 1 shows that after the vibration is completed, the temperature of the molten metal in the mold continues to drop to 1400°C, and the performance of the mullite brick is significantly reduced. This may be because the gas in the molten metal cannot be fully released. Therefore, the crystallization method selected in Example 1 is the best.

[0090] Experimental Example 4: Investigating the influence of preparation parameters of silicon nitride / calcium carbonate composite particles on the performance of mullite bricks

[0091] Using Example 1, Examples 14 to 19 and Comparative Example 4 as experimental comparisons, the performance of the mullite bricks obtained under different preparation parameters of the silicon nitride / calcium carbonate composite particles is shown in Table 4 below:

[0092] Table 4 Properties of mullite bricks under different preparation parameters of silicon nitride / calcium carbonate composite particles

[0093] Group Compressive strength / MPa Erosion rate Example 1 293 0.83 Embodiment 14 248 1.18 Embodiment 15 259 1.04 Example 16 275 0.96 Embodiment 17 263 1.01 Embodiment 18 253 1.06 Embodiment 19 261 0.98 Comparative Example 4 238 1.46

[0094] It can be seen from the data in Table 4 that, compared with Examples 1, 14, and 15: too high or too low pH value of the precursor solution will lead to a decrease in the performance of the mullite brick. This may be because the pH value of the precursor solution will affect the conversion rate of the silicon nitride / calcium carbonate composite particles. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the pH value of the precursor solution selected in Example 1 is the best;

[0095] Comparison of Examples 1, 16, and 17: The ratio of the precursor solution to calcium oxide will affect the performance of the mullite brick. This may be because the ratio of the precursor solution to calcium oxide will affect the bonding strength of the silicon nitride / calcium carbonate composite particles. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the ratio of the precursor solution to calcium oxide selected in Example 1 is the best;

[0096] Compared with Examples 1, 18, and 19: Too high or too low a flow rate of carbon dioxide will lead to a decrease in the performance of the mullite brick. This may be because the flow rate of carbon dioxide will affect the conversion rate of silicon nitride / calcium carbonate composite particles. Among them, the mullite brick of Example 1 has the highest compressive strength and the lowest erosion rate, indicating that the mullite brick of Example 1 has the best performance. Therefore, the carbon dioxide flow rate selected in Example 1 is the best;

[0097] Compared with Comparative Example 4, Example 1 does not adjust the pH value of the precursor solution, and the performance of the mullite brick is significantly reduced. This may be because the conversion rate of the silicon nitride / calcium carbonate composite particles is reduced after the pH value of the precursor solution is not adjusted. Therefore, the preparation method of the silicon nitride / calcium carbonate composite particles selected in Example 1 is optimal.

Claims

1. A method for preparing high-quality mullite bricks for glass kilns, characterized in that: The following steps are involved: S1. Ingredients By weight, 60 to 75 parts of mullite powder, 6 to 10 parts of magnesium oxide, 4 to 8 parts of zircon sand, 2 to 5 parts of ferrous bauxite, and 1 to 3 parts of sodium bicarbonate are mixed to obtain a mixture; S2, Melting The mixed material is placed in an electric arc furnace, heated to 2000-2200°C, and the mixed material is melted to obtain a molten liquid; S3. Pouring Preheat the mold, and then pour the molten metal into the mold so that the molten metal fully fills the mold cavity; S4, Crystallization S4-1, keeping the mold at 1800-1900°C for 30-40 minutes, adding silicon nitride / calcium carbonate composite particles to the melt once after the heat preservation is completed, then stopping the heat preservation and vibrating the mold once for 2-4 minutes, and waiting for the melt temperature in the mold to drop to X after the vibration is completed; wherein, the single addition amount of silicon nitride / calcium carbonate composite particles accounts for 0.3-0.6% of the total mass of the melt in the mold, and the initial value of X is 1600-1700°C; S4-2, repeat the cycle S4-1, and then each time the value of X is reduced by 50-80°C compared with the previous time, until X≤1400°C, so that the molten metal in the mold is quickly cooled to 800-850°C, and then the molten metal in the mold is naturally cooled to room temperature to obtain a mullite brick.

2. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S2, the melting and casting voltage of the electric arc furnace is 150-200V, and the current is 1800-2000A.

3. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S3, the preheating temperature is 400-480° C., and the preheating time is 20-30 minutes.

4. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S1, the aluminum-silicon ratio of the mullite powder is 1.3-1.6:1, and the particle size of the mullite powder is 1-3 mm.

5. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S4-1, the method for preparing the silicon nitride / calcium carbonate composite particles comprises the following steps: 1) Add silicon tetrachloride into xylene and stir for 5 to 10 minutes, then put the mixture of silicon tetrachloride and xylene into a closed reactor, and introduce liquid ammonia into the mixture to react for 1 to 2 hours, take the mixture out of the closed reactor, extract the unreacted liquid ammonia on the upper layer, and obtain a precursor solution; wherein the mass ratio of silicon tetrachloride, xylene, and liquid ammonia is 1:3 to 4:1.2 to 1.6; 2) adding calcium oxide and deionized water into the precursor solution, and then continuously passing carbon dioxide into the precursor solution. During the process of passing carbon dioxide, when the pH value of the precursor solution is less than 8, the pH value of the precursor solution is further adjusted to 9-10 using ammonia water with a mass concentration of 20-30%, and after aeration for 25-35 minutes, filtering to obtain solid particles; wherein the mass ratio of the precursor solution, calcium oxide, and deionized water is 1:0.3-0.4:0.6-0.8; 3) calcining the solid particles at 250-300° C. for 30-40 min to obtain silicon nitride / calcium carbonate composite particles.

6. The method for preparing high-quality mullite bricks for glass kiln according to claim 5, characterized in that: The flow rate of the carbon dioxide is 1 to 2 L / min.

7. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S4.1, the vibration frequency is 5 to 8 Hz, and the vibration amplitude is 2 to 4 mm.

8. The method for preparing high-quality mullite bricks for glass kiln according to claim 1, characterized in that: In step S4.3, the rapid cooling method is to use compressed air at 10 to 15°C to spray the mold surface, and the air flow speed of the spray is 4 to 6 m / s.